Pengaruh Kualitas Produk kartuHALO Terhadap Kepuasan Pengguna (Studi pada GraPARI Telkomsel MTC Bandung) - Puspitasari, Dita; Tjahjawati, Sri Surjani (Jurnal Riset Bisnis dan Investasi, 2016)
Every company does business by producing a product or service with good quality. Quality is very important for the company because every company has its own standards based on specifications set. The quality is also very important for consumers because consumers who determine the needs and desires as well as closely related to satisfaction will be felt after using the product. Customer satisfaction is also very important for the company because the company trying to provide something that is needed, desired and sought after by consumers, and ultimately the consumer will be satisfied. Satisfaction is also very important for consumers because it is something to be gained by comparing the expectations of the performance of the products that have been purchased. This study aims to determine the effect on product quality kartuHALO user satisfaction in GraPARI MTC Telkomsel Bandung. The method used in this research is descriptive method, with the results stating that kartuHALO product quality and user satisfaction in GraPARI MTC Telkomsel Bandung is quite good. Of the eight dimensions of the variable product quality, performance dimension had the highest contribution is 4.14 and the dimensions of durability contribute to the bottom at 3.86. For user satisfaction, from the existing three-dimensional, dimensions of emotional factors contribute to the high at 4.02 and dimensions contribute to its lowest price of 3.66. This study used a questionnaire distributed to 270 respondents. Based on the research that has been done, regression equation Y = 7.483 + 0,283X. The study states that kartuHALO product quality and user satisfaction has a strong positive correlation of 0.582 and product quality kartuHALO affect user satisfaction of 33.9%.